Preventing and Controlling COVID-19: A Practical-Based Review in Offshore Workplace - Sunandar, Hendar; Ramdhan, Doni Hikmat (UI Scholars Hub, 2021)
An offshore platform is a workplace with complex facilities and limited space due to the complex installed equipment and components. Therefore, the offshoreas enclosed area platform is more likely to have a high risk of COVID-19 outbreak. Furthermore, a company must strictly follow health protocols to preventworkers from being exposed to COVID-19 in the offshore workplace. However, workers are often forced to onboard without proper health protocols becauseof operational needs and production targets. This paper aimed to explore the essence of the steps in preventing and controlling COVID-19 in the offshoreworkplace and the challenges. The analysis found that the company must take preventive measures against COVID-19 before workers are on board and inthe workplace and control it using the hierarchy of control: engineering control, administrative control, and personal protective equipment (PPE).